2010
DOI: 10.2166/wst.2010.821
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus, MS2 and PhiX174 interactions with drinking water biofilms developed on PVC, cement and cast iron

Abstract: Biofilms colonizing pipe surfaces of drinking water distribution systems could provide habitat and shelter for pathogenic viruses present in the water phase. This study aims (i) to develop a method to detect viral particles present in a drinking water biofilm and (ii) to study viral interactions with drinking water biofilms. A pilot scale system was used to develop drinking water biofilms on 3 materials (7 cm(2) discs): PVC, cast iron and cement. Biofilms were inoculated with viral model including MS2, PhiX174… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this study, we identified two roles of biofilms in mediating the fate of SARS-CoV-2 RNA in sewers: firstly, biofilms could facilitate RNA biodegradation, which might cause RNA signal loss over long HRTs; secondly, biofilms form a reservoir for viral RNA, protecting virus fragments from being washed off during hydraulic changes, and subsequently releasing RNA fragments back to surrounding wastewater. This suggested that the fate of SARS-CoV-2 RNA in sewers was a dynamic equilibrium between adsorption, decay, desorption and detachment of RNA associated with biofilms, similar to findings of previous studies for other bacterial and viral indicators 8,21 . According to observations in this study, the adsorption and accumulation of SARS-CoV-2 RNA onto biofilms played a dominant role, particularly with respect to degradation, leading to the persistence of RNA in a sewer section after several wastewater replacements.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we identified two roles of biofilms in mediating the fate of SARS-CoV-2 RNA in sewers: firstly, biofilms could facilitate RNA biodegradation, which might cause RNA signal loss over long HRTs; secondly, biofilms form a reservoir for viral RNA, protecting virus fragments from being washed off during hydraulic changes, and subsequently releasing RNA fragments back to surrounding wastewater. This suggested that the fate of SARS-CoV-2 RNA in sewers was a dynamic equilibrium between adsorption, decay, desorption and detachment of RNA associated with biofilms, similar to findings of previous studies for other bacterial and viral indicators 8,21 . According to observations in this study, the adsorption and accumulation of SARS-CoV-2 RNA onto biofilms played a dominant role, particularly with respect to degradation, leading to the persistence of RNA in a sewer section after several wastewater replacements.…”
Section: Discussionsupporting
confidence: 87%
“…While previous studies have convincingly presented the evidence that biofilms can harbor pathogens (Flemming and Wingender, 2010; Altman et al, 2009; Helmi et al, 2010, 2008; Kumar and Anand, 1998), systematic studies to identify the physical and chemical factors controlling pathogen attachment to biofilm are rare. For example, Escherichia coli and fluorescent polystyrene beads have been found to attach more to biofilms grown from tap water on glass slides than to the surface of clean glass slides (Paris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An eluting protocol was then carried out as previously described (Helmi et al . ). Briefly, each coupon was immersed in 20 ml of elution buffer containing beef extract (1%) and glycine (50 mmol l −1 ) adjusted to pH 9; probe sonication was carried out twice on ice for 1 min at 20–25 W (Vibra‐cell).…”
Section: Methodsmentioning
confidence: 97%